Pressure Ionization, Polarizability and Screening Constants in Confined Hydrogen Like Ions of Astrophysical Importance (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2021)
An extensive non-relativistic study of the confined Hydrogenic ions of Astrophysical importance like CVI, NVII and OVIII is made in the framework of a simple model of a spherical penetrable box. The detailed calculations of the energy eigenvalues of these ions have been performed. The variation of the energy levels with the spatial restrictions in the form of the variation in the confinement radii or size of the box and the strength of the penetrable wall is investigated. The solution of the radial Schrodinger equation is done numerically using the highly efficient Numerov method which is generally employed to solve the second order ordinary differential equations without the first order term. A point worth mentioning is that with the decrease in confinement radius, the bound state transformed into continuum states, resulting Pressure ionization which we find in Astrophysical Objects under extreme pressure. We also find effect of confinement on several useful quantities like polarizability and Screening constants.
Keywords: Confined atoms; Pressure ionization; Polarizability; Numerov method